Racing the clock: Recent developments and open environmental regulatory issues at the International Seabed Authority on the eve of deep-sea mining. (June 2022) - Ardito, Giovanni; Rovere, Marzia
Abstract: With a letter dated 25th June 2021, Nauru has triggered section 1, paragraph 15, of the 1994 Agreement relating to the Implementation of Part XI of the United Nations Convention on the Law of the Sea, by which it requested the Council of the International Seabed Authority to adopt the regulations to facilitate the approval of a plan of work for the exploitation of the mineral resources of the Area within 2 years. The two-year rule rises many legal and policy issues that the Authority is required to deal with in the next months. Among them, this communication dwells upon the consequences of the provisional approval of plans of work, in case the Authority was unable to approve the exploitation regulations by 2023. It then considers the outstanding environmental regulatory issues of the mining code that are still under discussion, with peculiar regard to the precautionary principle, the environmental impact assessment, and the need for an inspection mechanism and suggests possible ways forward.